Plant biomass conversion - Hood, Elizabeth; Nelson, Peter (Peter Allan), 1974-; Powell, Randy; Wiley InterScience (Online service) (Chichester ; Hoboken, NJ : Wiley-Blackwell, 2011)
As concerns regarding increasing energy prices, global warming and renewable resources continue to grow, so has scientific discovery into agricultural biomass conversion. Plant Biomass Conversion addresses both the development of plant biomass and conversion technology, in addition to issues surrounding biomass conversion, such as the affect on water resources and soil sustainability. This book also offers a brief overview of the current status of the industry and examples of production plants being used in current biomass conversion efforts.
The Bioeconomy: A New Era of Products Derived from Renewable Plant-Based Feedstocks / Peter Nelson, Elizabeth Hood, Randall Powell -- Agricultural Residues / James Hettenhaus -- Growing Systems for Traditional and New Forest-Based Materials / Randall Rousseau, Janet Hawkes, Shijie Liu, Tom Amidon -- Dedicated Herbaceous Energy Crops / Keat (Thomas) Teoh, Shivakumar Pattada Devaiah, Deborah Vicuna Requesens, Elizabeth E Hood -- Municipal Solid Waste as a Biomass Feedstock / David J Webster -- Water Sustainability in Biomass Cropping Systems / Jennifer L Bouldin, Rodney E Wright -- Soil Sustainability Issues in Energy Crop Production / V Steven Green -- Fermentation Organisms for 5- and 6-Carbon Sugars / Nicholas Dufour, Jeffrey Swana, Reeta P Rao -- Pretreatment Options / Bradley A Saville -- Enzyme Production Systems for Biomass Conversion / John A Howard, Zivko Nikolov, Elizabeth E Hood -- Fermentation-Based Biofuels / Randy Kramer, Helene Belanger -- Biobased Chemicals and Polymers / Randall W Powell, Clare Elton, Ross Prestidge, Helene Belanger -- Carbon Offset Potential of Biomass-Based Energy / Gauri-Shankar Guha -- Biofuel Economics / Daniel Klein-Marcuschamer, Brad Holmes, Blake A Simmons, Harvey W Blanch.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Biomass conversion; Human ecology -- Study and teaching; Biomass conversion; Human ecology -- Study and teaching; Electronic books